2014
DOI: 10.1002/acn3.64
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal abnormalities in hereditary spastic paraplegia types SPG 15 and SPG 11

Abstract: ObjectiveHereditary spastic paraplegias (HSPs) are among the most genetically diverse inherited neurological disorders, with over 70 disease loci identified (SPG1-71) to date. SPG15 and SPG11 are clinically similar, autosomal recessive disorders characterized by progressive spastic paraplegia along with thin corpus callosum, white matter abnormalities, cognitive impairment, and ophthalmologic abnormalities. Furthermore, both have been linked to early-onset parkinsonism.MethodsWe describe two new cases of SPG15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
81
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 33 publications
16
81
1
Order By: Relevance
“…The accumulation of enlarged LPOs in spastizin-or spatacsin-depleted cells led us to investigate any impairment in lysosome-dependent autophagy. Indeed, accumulation of autophagosomes has been observed in fibroblasts derived from patients with SPG15 and SPG11 (12,13). Furthermore, mature autophagosomes, as visualized by immunostaining for p62 or and autophagic defects in spastizin-and spatacsin-depleted HeLa cells as well as fibroblasts from patients with AR-HSP-TCC.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…The accumulation of enlarged LPOs in spastizin-or spatacsin-depleted cells led us to investigate any impairment in lysosome-dependent autophagy. Indeed, accumulation of autophagosomes has been observed in fibroblasts derived from patients with SPG15 and SPG11 (12,13). Furthermore, mature autophagosomes, as visualized by immunostaining for p62 or and autophagic defects in spastizin-and spatacsin-depleted HeLa cells as well as fibroblasts from patients with AR-HSP-TCC.…”
Section: Introductionmentioning
confidence: 95%
“…In contrast, endogenous spastizin immunolabeling overlapped minimally with the early endosomal marker early endosomal antigen 1 (EEA1) and only partially with the late endosomal marker cation-independent mannose-6-phosphate receptor (CI-MPR) ( Figure 1E). To confirm the specificity of endogenous spastizin labeling, we compared spastizin immunostaining in control fibroblasts with that in cells from a patient with SPG15 lacking spastizin protein (13). Lysosomal labeling in wild-type fibroblasts was similar to that in HeLa cells, but the immunoreactive signal was nearly undetectable in SPG15 patient cells, indicating that the robust staining represents bona fide spastizin ( Figure 1F).…”
Section: Spg15 Protein Spastizin Localizes To Lysosomes Via Its Fyvementioning
confidence: 99%
See 2 more Smart Citations
“…Because of the lack of relevant disease models, the underlying molecular mechanisms and, in particular, the neuronal functions of spatacsin are still unclear. Previous studies employing non‐neuronal cellular models suggested stress‐related impairments within the lysosomal‐autophagy pathway attributed to loss of function of spatacsin in HeLa cells and patient‐derived fibroblasts 10, 11. We recently reported that SPG11‐iPSC‐derived patient neurites exhibited neurodegenerative changes on a functional and ultrastructural level 12…”
mentioning
confidence: 97%